DNA encoding an HIV-1 Gag/human lysosome-associated membrane protein-1 chimera elicits a broad cellular and humoral immune response in Rhesus macaques. - Priya Chikhlikar; Luciana Barros de Arruda; Milton Maciel; Peter Silvera; Mark G Lewis; J Thomas August; Ernesto T A Marques (PLoS ONE)
Previous studies of HIV-1 p55Gag immunization of mice have demonstrated the usefulness of targeting antigens to the cellular compartment containing the major histocompatibility complex type II (MHC II) complex molecules by use of a DNA antigen formulation encoding Gag as a chimera with the mouse lysosome-associated membrane protein (mLAMP/gag). In the present study, we have analyzed the magnitude and breadth of Gag-specific T-lymphocyte and antibody responses elicited in Rhesus macaques after immunization with DNA encoding a human LAMP/gag (hLAMP/gag) chimera. ELISPOT analyses indicated that the average Gag-specific IFN-gamma response elicited by the hLAMP/gag chimera was detectable after only two or three naked DNA immunizations in all five immunized macaques and reached an average of 1000 spot-forming cells (SFC)/10(6) PBMCs. High IFN-gamma ELISPOT responses were detected in CD8(+)-depleted cells, indicating that CD4(+) T-cells play a major role in these responses. The T-cell responses of four of the macaques were also tested by use of ELISPOT to 12 overlapping 15-amino acids (aa) peptide pools containing ten peptides each, encompassing the complete Gag protein sequence. The two Mamu 08 immunized macaques responded to eight and twelve of the pools, the Mamu B01 to six, and the other macaque to five pools indicating that the hLAMP/gag DNA antigen formulation elicits a broad T-cell response against Gag. Additionally, there was a strong HIV-1-specific IgG response. The IgG antibody titers increased after each DNA injection, indicating a strong amnestic B-cell response, and were highly elevated in all the macaques after three immunizations. Moreover, the serum of each macaque recognized 13 of the 49 peptides of a 20-aa peptide library covering the complete Gag amino acid sequence. In addition, HIV-1-specific IgA antibodies were present in the plasma and external secretions, including nasal washes. These data support the findings of increased immunogenicity of genetic vaccines encoded as LAMP chimeras, including the response to DNA vaccines by non-human primates.